THE ANALYSIS OF CODE MIXING IN FILM FROM BANDUNG WITH LOVE - Elisabet Sipayung; Meisuri Meisuri (LINGUISTICA, 2013)
ABSTRACT   This research aims to get information of sociolinguistics about code mixing in a film titled From Bandung with Love uttered by the characters. The characters use some types of code mixing. The main type is Intra Lexical Code Mixing. The results of this research are (1) There are three types of code mixing in the film, (2)The most type which has big effect is Lexical (3) Lexical code mixing as the dominant type shows that the teenagers in Indonesia like to mix their language per word to show that they are educated and modern.       Keywords : Sociolinguistics, code mixing, From Bandung with Love